Generating Innovative Ideas for School Improvement: An Examination of School Principals - Miguel M. Gonzales; Tiberio Garza; Elizabeth Leon-Zaragoza (MDPI AG, 2024)
The purpose of this exploratory study was to examine school principals' tendencies and practices that bring forth innovative ideas for school improvement. School principals (N = 124) responded to a survey, which included an open-ended question, on their innovative practices toward school improvement. With the Innovator's DNA framework as a basis for generating innovation for school improvement, path analysis was used to assess how well school principals' thinking and practices aligned with the framework. School principals believed it was important to help generate innovation through idea networking, being open-minded, and challenging the status quo. However, through path analysis, school principals' improvement areas associated with the Innovator's DNA framework were identified. School systems should help principals develop innovative problem-solving skills for school improvement by applying the Innovator's DNA framework in their professional development opportunities. More research is needed that examines if and how school systems foster school innovation leadership for principals.